The profile analysis and selection guide for the heat source on the finished surface in grinding. (December 2017) - Wang, Dexiang; Sun, Shufeng; Jiang, Jingliang; Liu, Xinfu
Abstract: To perform grinding temperature field analysis, the heat source on the finished surface is more convenient compared with the heat source on the workpiece/wheel contact surface. Therefore, many profiles of the heat source on the finished surface were proposed. However, these profiles were based on the specific grinding conditions, and were not universally applicable. In this research, the changing trend of the PHSF (profile of the heat source on the finished surface) under different grinding conditions was investigated. The contact angle and the Peclet Number are two critical parameters to clarify the changing trend. At small contact angles, the PHSF is right triangular. Under the conditions of very low Peclet Numbers and large contact angles, the PHSF is triangular. Under the conditions of large contact angles and high Peclet Numbers, the PHSF is parabolic. Two PHSFs were proposed and were described by mathematical formulas. A figure to serve as the selection guide for the two PHSFs was obtained, which took the error of the maximum dimensionless temperature less than 15% as the engineering permissible range. The figure contains almost all the general grinding conditions, and can be conveniently used in engineering for the grinding temperature analysis.